Frontispiece: Electrically Activated Conductivity and White Light Emission of a Hydrocarbon Nanoring–Iodine Assembly. Issue 37 (29th August 2017) - Ozaki, Noriaki; Sakamoto, Hirotoshi; Nishihara, Taishi; Fujimori, Toshihiko; Hijikata, Yuh; Kimura, Ryuto; Irle, Stephan; Itami, Kenichiro
Abstract : Smart Materials In their Communication onpage 11196 ff., H. Sakamoto, K. Itami et al. show that an electric‐stimuli‐responsive multifunctional material is obtained by mixing a hydrocarbon nanoring ([10]cycloparaphenylene) and iodine.